As CEBs no Rio Grande do Sul: o caso do bairro Mathias Velho município de Canoas (1975 - 1988) - Machado, Odilon Kieling (2012)
This research aims to identify and analyze the relationship between the Basic Ecclesial Communities (CEBs - Comunidades Eclesiais de Base) and religious, social and political lives of the residents of Mathias Velho Neighborhood, in Canoas, Rio Grande do Sul, between 1975 and 1988, from the participation of Marist Brother Antônio Cechin and popular educator Matilde Cechin. The CEBs are an ecclesial organization with socio-political dimensions, considered both as a new area of religious experience and an instrument for social struggles of the working classes. The CEBs have their origins in the changes that occur in the Catholic Church from the Second Vatican Council, and in particular, the Conference of Medellin, with the preferential evangelical option for the poor". These communities are spread in Brazil, in a context of authoritarian military governments, and we focus our research in the CEBs who settled in the Mathias Velho Neighborhood. Informed by the Liberation Theology and inserted into the project of a new church, Brother Antônio and Matilde Cechin worked among the poor of Mathias Velho, between 1975 and 1988. This action results in the formation of social movements that carry out the occupation of land and the creation of Santo Operário and União dos Operários Villages. This paper seeks to identify the residents of Old Mathias as historical subjects in a context of social diversity, social movement agents of community characteristics, driven by the CEBs. The struggle for labor, employment and income is the main goal of the population who reaches Canoas. The organization of mothers' clubs, neighborhood associations, community garden and oven, plus specific demands such as water, electricity, transport and streets are results obtained by the social movement, built by the residents themselves, from the "seed" launched by religious agents Antônio and Matilde. As research methodology, we consulted existing literature about the period, as well as about Canoas and the CEBs, along with research in the personal collection of the main religious leaders. We also conducted interviews with Brother Antônio Cechin, popular educator Matilde Cechin, Father Pedrinho Guareschi, Friar Wilson Dallagnol and lawyer Jacques Alfonsin - all involved with the CEBs and social movements in Mathias Velho Neighborhood. We understand that the issue is relevant to the history of social movements and also for studies on religiosity, as it focuses on social movements from religious motivations. In the case, motivations which have their origins in transformations experienced by the Catholic Church, especially by the emergence and spreading of Liberation Theology and the CEBs.